2020
DOI: 10.2169/internalmedicine.3582-19
|View full text |Cite
|
Sign up to set email alerts
|

Single Rectal Neuroendocrine Tumor Associated with Multiple Endocrine Cell Micronests

Abstract: Although a few reports of neuroendocrine tumor (NET) in the stomach or appendix with surrounding micronests have been published, cases of rectal NET are rare. We herein report a unique case of a patient with single rectal NET treated endoscopically. A pathological examination revealed multiple endocrine cell micronests (ECMs) in the submucosal layer around the main NET lesion. Neither lymph node metastasis nor distant metastasis in computed tomography was observed six years after the treatment. Because case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In the current report, 2 cases with ≥4 lesions had ECM (Table 1 ), and there was no LNM. Similar to our 2 cases, some studies reported that cases with ECM did not have metastasis or recurrence [ 4 , 8 ]. A further large-scale study including genetic analysis should be performed to clarify the characteristics of ECM.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the current report, 2 cases with ≥4 lesions had ECM (Table 1 ), and there was no LNM. Similar to our 2 cases, some studies reported that cases with ECM did not have metastasis or recurrence [ 4 , 8 ]. A further large-scale study including genetic analysis should be performed to clarify the characteristics of ECM.…”
Section: Discussionsupporting
confidence: 89%
“…Most rectal NETs show a single lesion; however, there are some reports about multiple lesions [ 3 , 8 , 9 , 10 ]. It is not well understood why multiple lesions develop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations